Use of tumor mutational burden as a predictive marker of response to immuno-oncology agents: Initial experience at an academic center in Venezuela - Sucre, Santiago; Sucre, Oscar; Vivas, Liliam; Salazar, Hector; Sucre, Carlos Eduardo (Journal of clinical oncology, 2023)
e14613Background: Tumor Genetic Profiling (TGP) is steadily becoming the mainstay of clinical practice, namely, the Tumor Mutational Burden (TMB) is believed to be a predictor of efficacy to treatment with Immune Checkpoint Inhibitors (ICI). Recent studies have demonstrated that a high-TMB score (TMB-H) is associated with higher response rates. In Venezuela, the evidence of mutational frequencies obtained by TGP is limited, herein we present our experience at a large educational institution. Methods: In this retrospective cohort, we included 80 subjects with different types of solid tumors to whom TGP was performed to determine TMB values, as well as other associated mutations, between January 2020 and December 2022. In a subgroup of subjects in which ICI therapy was formally indicated (n=21) we used the Objective Response Rate (ORR) as a primary endpoint, recorded as the percentage of patients who had a complete response (CR) or partial response (PR), based on the RECIST v1.1 criteria. Treatment options included Ipilimumab, Atezolizumab, Pembrolizumab and Nivolumab, as either monotherapy or in combination according to the corresponding NCCN guidelines. A TMB-H score was defined as greater than 10 mutations per megabase. Results: A TMB-H was found in 11 samples, subjects with lung cancer accounted for the majority of this finding (n=6). The most frequently reported mutations were BRCA 1-2 (n=9), KRAS (n=9), and EGFR (n=4). In the subgroup treated with ICI, the ORR of the group with TMB-H was 71.42%, while in those with low TMB it was 35.71%. The differences in response rates, with a 95% CI, yielded a p=0.122; which corresponds to a statistically non-significant outcome. Conclusions: This study constitutes the first country-level documentation of what is becoming a standardized practice, and contributes to the growing evidence regarding the use of TMB-H as a marker to predict response to treatment. Our small cohort demonstrated a high ORR to ICI when a TMB-H score is present, albeit to a non-statistically significant degree. We will continue to follow-up these patients, as well as to include newly sequenced samples for TGP, to give greater statistical power to these findings.